2021
DOI: 10.1136/bmjnph-2021-000253
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in the severity of COVID-19 illness by race and ethnicity

Abstract: IntroductionEarly reports highlighted racial/ethnic disparities in the severity of COVID-19 seen across the USA; the extent to which these disparities have persisted over time remains unclear. Our research objective was to understand temporal trends in racial/ethnic variation in severity of COVID-19 illness presenting over time.MethodsWe conducted a retrospective cohort analysis using longitudinal data from Cedars-Sinai Medical Center, a high-volume health system in Southern California. We studied patients adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
1
7
0
2
Order By: Relevance
“…Many elderly patients were excluded because of acute or chronic cognitive impairment, which resulted in a relatively limited study population. For practical reasons, only Swedish and English-speaking patients were included, which might have ruled out patients known to have an increased risk of developing severe COVID-19 ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many elderly patients were excluded because of acute or chronic cognitive impairment, which resulted in a relatively limited study population. For practical reasons, only Swedish and English-speaking patients were included, which might have ruled out patients known to have an increased risk of developing severe COVID-19 ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Men usually have better blood lead degrees than women [43]. Study finished via way of means of Ebinger JE et al [44] confirmed that extra COVID-19 severity remains skilled amongst Hispanic/Latinx patients.…”
Section: Discussionmentioning
confidence: 91%
“…Of these 59 studies, 18 (30.5%) were conducted across the USA [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Eight studies were conducted in Michigan [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], six in New York [ 45 , 46 , 47 , 48 , 49 , 50 ], four in Atlanta [ 51 , 52 , 53 , 54 ], and four in California [ 55 , 56 , 57 , 58 ]. The remaining studies were divided as follows: one in three states (California, Oregon, and Washington) [ 59 ], one in Massachusetts [ 60 ], one in Tennessee [ 61 ], two in Wisconsin [ 62 , 63 ], one in Mississippi [ 64 ], one in Cleveland [ 65 ], one in Pennsylvania [ 66 ], two in Louisiana [ 67 , 68 ], one in the Midwest [ 69 ], one near the Mexico border [ 70 ], one in New Orleans [ ...…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the study design, the selected 59 studies can be categorized into studies that were retrospective in nature, cross-sectional in nature, association studies, case-control studies, and cohort studies. There were 45 studies that were retrospective in nature, including observational studies [ 19 , 20 , 22 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 43 , 44 , 46 , 47 , 49 , 51 , 52 , 53 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 68 , 70 , 71 , 72 , 76 ]. Additionally, there was one association study [ 37 ], seven cohort studies [ 21 , 24 , 25 , 28 , 45 , 54 , 73 ], five cross-sectional studies [ 23 , 55 , 63 , 74 , 77 ], and one case-control study [ 48 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation